Abbreviated Magnetic Resonance Imaging With Breath‐Hold Three‐Dimensional Magnetic Resonance Cholangiopancreatography: Assessment of Malignant Risk of Pancreatic Intraductal Papillary Mucinous Neoplasm. Issue 4 (28th March 2021) - Yoo, Jeongin; Min, Ji Hye; Lee, Dong Ho; Hur, Bo Yun; Kim, Se Woo; Kim, Eunju
Abstract : Background: For surveillance of pancreatic intraductal papillary mucinous neoplasms (IPMNs), magnetic resonance imaging (MRI)/magnetic resonance cholangiopancreatography (MRCP) is preferred over computed tomography, but the long acquisition time limits its use. Purpose: To investigate the diagnostic performance of abbreviated MRI with breath‐hold (BH) three‐dimensional MRCP (abbreviated MRI‐BH) for malignant risk assessment of pancreatic IPMN. Study Type: Retrospective. Population: Two hundred and thirty‐five patients with IPMNs (M:F = 115:120; mean age ± SD, 66 ± 9 years; typical imaging features with ≥2‐year stability [ N = 172] and histopathologically confirmed [ N = 63]). Field Strength/Sequence: 3.0 T/ abbreviated MRI‐BH (single‐shot fast spin‐echo, T1W fat‐suppressed gradient‐echo sequence, and BH‐3D‐MRCP). Assessment: Abbreviated MRI‐BH was reviewed by three reviewers, and its diagnostic performance was assessed using the predetermined scoring system. The diagnostic performance for the mural nodule detection was assessed. Additionally, diagnostic performance of abbreviated MRI was compared with that of full‐sequence MRI. Statistical Tests: Area under the receiver operating characteristic curve (AUC) with z ‐test, and linear‐weighted kappa values. Results: Thirty‐five patients had malignant IPMN. At a cut‐off score ≥3, AUCs of abbreviated MRI‐BH for detecting malignant IPMN were 0.959 for reviewer 1, 0.962 for reviewer 2, and 0.956 for reviewer 3. The sensitivity of reviewers 1, 2, and 3 was 97.1% for all, and the specificity was 85.5%, 86.0%, and 85.0%, respectively. Regarding mural nodule detection ( N = 22), abbreviated MRI‐BH demonstrated a sensitivity of 95.5% and a specificity of 88.3% for reviewer 1, a sensitivity of 86.4% and a specificity of 92.0% for reviewer 2, and a sensitivity of 86.4% and a specificity of 89.2% for reviewer 3. There were no significant differences between AUC of abbreviated MRI‐BH and that of full‐sequence MRI in the three reviewers ( P > 0.05). Data Conclusion: Abbreviated MRI‐BH showed good diagnostic performance for detecting malignant IPMNs by using a predetermined scoring system. Level of Evidence: 3 Technical Efficacy Stage: 2